The Role of Attitudinal Loyalty, Behavioral Loyalty, Sponsor Awareness, and Attitude Toward Sponsorship in Creating Purchase Intention on Specs - Santi Rimadias; Lisa Faradila (Jurnal Ilmu Manajemen & Ekonomika, 2019)
The JakMania Jakarta is one of the football club's supporters in Indonesia. This research aims to analyze the determinants of Specs purchase intention within the Jakmania Jakarta Supporters perception, such as attitudinal loyalty, behavioral loyalty, sponsor awareness, and attitude toward sponsorship. Data collection methods used in this research were surveyed by disseminating a questionnaire to the 100 respondents who members of the JakMania Jakarta Supporters. The analysis of the data used Structural Equation Model (SEM). The results showed that attitudinal loyalty, behavioral loyalty, and attitude towards the sponsor have a positive influence to purchase intention on specs. Behavioral loyalty and attitude towards the spon-sor have a positive influence on sponsorship awareness. Behavioral loyalty has a positive influence on atti-tude towards the sponsor, and attitudinal loyalty has a positive influence on behavioral loyalty. Meanwhile, attitudinal loyalty has no influence on sponsorship awareness and attitude towards the sponsor. Last, spon-sorship awareness does not influence purchase intention on specs.